Pockmarks in the Witch Ground Basin, Central North Sea. (1st April 2019) - Böttner, Christoph; Berndt, Christian; Reinardy, Benedict T.I.; Geersen, Jacob; Karstens, Jens; Bull, Jonathan M.; Callow, Ben J.; Lichtschlag, Anna; Schmidt, Mark; Elger, Judith; Schramm, Bettina; Haeckel, Matthias
Abstract: Marine sediments host large amounts of methane (CH4), which is a potent greenhouse gas. Quantitative estimates for methane release from marine sediments are scarce, and a poorly constrained temporal variability leads to large uncertainties in methane emission scenarios. Here, we use 2‐D and 3‐D seismic reflection, multibeam bathymetric, geochemical, and sedimentological data to (I) map and describe pockmarks in the Witch Ground Basin (central North Sea), (II) characterize associated sedimentological and fluid migration structures, and (III) analyze the related methane release. More than 1, 500 pockmarks of two distinct morphological classes spread over an area of 225 km 2 . The two classes form independently from another and are corresponding to at least two different sources of fluids. Class 1 pockmarks are large in size (>6 m deep, >250 m long, and >75 m wide), show active venting, and are located above vertical fluid conduits that hydraulically connect the seafloor with deep methane sources. Class 2 pockmarks, which comprise 99.5% of all pockmarks, are smaller (0.9–3.1 m deep, 26–140 m long, and 14–57 m wide) and are limited to the soft, fine‐grained sediments of the Witch Ground Formation and possibly sourced by compaction‐related dewatering. Buried pockmarks within the Witch Ground Formation document distinct phases of pockmark formation, likely triggered by external forces related to environmental changes after deglaciation. Thus, greenhouse gas emissions from pockmark fields cannot be based on pockmark numbers and present‐day fluxes but require an analysis of the pockmark forming processes through geological time. Plain Language Summary: Marine sediments host large amounts of methane (CH4), which is a potent greenhouse gas. The amount of methane released into the atmosphere is, however, largely unknown making it difficult to implement this methane source in climate models. Here we use geophysical, geochemical, and sedimentological data to map the distribution of fluid escape structures in the central North Sea. More than 1, 500 pockmarks, which are circular to semicircular depressions of the seafloor, indicate fluid flow from the subsurface. There are two distinct morphological classes of pockmarks corresponding to at least two different fluid sources. Class 1 pockmarks are large, show active venting, and are located above vertical fluid conduits in the subsurface, which feed fluids from deeper strata. Class 2 pockmarks, which comprise 99.5% of all pockmarks, are smaller and limited to the soft sediments directly below the seafloor. Older pockmarks in the subsurface document distinct phases of pockmark formation, likely triggered by external forces after the retreat of ice in the North Sea. The amount of methane released from natural geological sources based on pockmark numbers may be wrong as these do not take into account the origin and composition of released fluids. Key Points: Marine geophysical data document >1, 500 pockmarks of two morphological classes in the Witch Ground Basin, central North Sea Class 1 pockmarks are continuously active and supplied through seismic pipe structures by deeply sourced methane Class 2 pockmarks form at specific stratigraphic horizons suggesting intermittent venting triggered by pressure and temperature changes